How Small-Scale Farmers Understand Rain Water Harvesting Technology? Evidence from Northern Ethiopia - Abay Tafere Mengistu (The Scientific World Journal)
The study examined farmers’ perceptions and adoption of rain water harvesting technology in Raya-Alamata district of Ethiopia. Four kebeles were purposively selected from the 13 homogeneous kebeles (small administrative unit). During the survey, primary data were collected through a semistructured questionnaire distributed to 270 systematically selected sample respondents and through interview with key informants, development agents, and local administrators. Secondary data were retrieved from district agriculture office, books, and published scientific materials. Descriptive statistics, simple narration, and a probit regression model were used to analyze the data. The results showed that the farmers perceived rain water harvesting as a motivational way of creating sense of belongingness. They think that it increases crop production, increases forest regeneration, and encourages forage production. The probit regression models revealed that determinants of farmers’ adoption of rainwater harvesting technology were significantly and positively affected by education, farm size, and off-farm income. The effect of distance to the farmland and farmers training center (FTC) was also significant but negative. Men farmers had higher level of adoption compared to their counterparts. Productive and reproductive roles constrain women household farmers from using the technologies. Based on the finding, the policy implications were as follows: dissemination of information related to rain water harvesting technology should be imperative through formal and informal education. Alternative sources of water need also be promoted. More importantly, female-headed households need to be encouraged to be community leaders to foster the adoption of rain water harvesting technology.